(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Essential oils from eleven plant species belonging to the Asteraceae, Lamiaceae, Lauraceae and Myrothamnaceae families growing in Tanzania were screened for mosquito larvicidal and anti-candida activities, and were subjected to the brine shrimp lethality test. In the larvicidal and brine shrimp tests, the organisms were exposed to varying oil concentrations for 24 h, after which mortality was assessed. The anticandida activity was determined using the bioautography agar overlay method. All oils showed larvicidal activity with two Ocimum suave oil samples being the most active with LC50 values of 169.8 and 151.3 ppm. The same Ocimum suave oils also exhibited the highest brine shrimp mortality (LC50 4.0 and 12.6 ppm). Most of the oils showed anti-candida activity, with oils from Ocimum species being the most active compared to the others. Thus, Ocimum suave oils merit further investigation towards the development of safe and biodegradable larvicides. Furthermore, oils from Ocimum basilicum and Ocimum kilimandscharicum could offer useful alternatives for combating candidiasis, a common opportunistic infection in HIV/AIDS patients.